Copper-carbon-carbon heat conduction material and preparation method thereof
Through the coordinated use of CVD diamond and graphene, combined with the layer-by-layer rolling and vacuum hot pressing sintering process of copper foil and graphene, the problem of low thermal conductivity in copper-carbon composite materials is solved, and efficient thermal conductivity is achieved and Improved mechanical properties, suitable for the heat dissipation needs of high-power and high-density chips.
Patent Information
- Application Number
- CN202411382685.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
Among the existing copper-carbon composite materials, diamond or graphene cannot effectively improve the thermal conductivity effect. It is mainly due to the insufficient continuity of diamond or graphene in the material along the heat conduction direction, which leads to low thermal conductivity and is difficult to meet the needs of high-power and high-density chips. Heat dissipation needs.
Through the coordinated use of CVD diamond and graphene, a continuous through-channel in the heat conduction direction is formed. Combined with the layer-by-layer rolling and vacuum hot pressing sintering process of copper foil and graphene, copper-carbon-carbon thermal conductivity materials are prepared to improve the material thermal conductivity and mechanical properties.
It has achieved the improvement of the efficient thermal conductivity of the material, improved the heat dissipation uniformity and mechanical properties, overcome the problems of small size and high price of a single carbon-based thermal conductivity material, and is suitable for the heat dissipation needs of high-power and high-density chips.
Smart Images

Figure CN119189444A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat conducting material, in particular to a copper-carbon-carbon heat conducting material. Background Art
[0002] With the rapid development of computers, artificial intelligence, new energy vehicles and other fields in recent years, the requirements for chip power and power density have gradually increased, and the resulting heat dissipation requirements have become more stringent. Among the currently used heat dissipation materials, metal and silicon-based ceramic materials are the main ones. However, their heat dissipation efficiency is low, and the thermal conductivity of the material is usually around 400W / (m·K), which is difficult to meet the heat dissipation requirements of high-power and high-density chips.
[0003] Diamond is the hardest material in the world. In addition to its excellent mechanical properties, it also has good thermal and electrical properties. The thermal conductivity of diamond can reach 2200W / (m·K) and 5.7×10 6 With a breakdown voltage field of 100 V / cm, extremely high thermal conductivity and good resistance, it is an excellent material for preparing chip heat dissipation devices. Some people call it the "ultimate material" for heat dissipation devices. However, due to the limitation of technological development level, pure diamond heat dissipation materials often have disadvantages such as small size, poor mechanical properties and too high price, which makes them difficult to be used in actual production.
[0004] Graphene is a two-dimensional carbon material, and its in-plane thermal conductivity can reach or even exceed that of diamond. According to current test results, its in-plane thermal conductivity can reach 5300W / (m·K). However, due to the particularity of its two-dimensional structure, its inter-layer thermal conductivity is less than 200W / (m·K), which greatly affects its use as a thermal conductive material. At the same time, the relatively poor mechanical properties of graphene have also hindered its application progress to a certain extent.
[0005] At present, in order to improve thermal conductivity, various copper-carbon composite materials are most commonly used, among which copper-diamond is more common and copper-graphene is slightly less common. However, there are certain problems in all of them. The main reason is that the above materials cannot achieve the continuity of diamond or graphene in the material along the direction of heat conduction, which greatly reduces the thermal conductivity of the above two carbon materials. Taking copper-diamond material as an example, the current highest thermal conductivity is within 700W / (m·K), and the role of diamond is not effectively played. Summary of the invention
[0006] In view of the fact that diamond or graphene cannot effectively improve the thermal conductivity of the current copper-carbon composite thermal conductive material, CVD diamond and graphene are used to synergistically improve the thermal conductivity of the material, so that diamond and graphene form a continuous through channel in the heat conduction direction, thereby truly improving the thermal conductivity of the carbon material in the final product. The present invention also provides a method for preparing the above copper-carbon-carbon thermal conductive material.
[0007] To achieve the above object, the present invention is achieved through the following technical solutions: A copper-carbon-carbon thermal conductive material is a cylindrical material formed by rolling copper foil and graphene along the outer circle of CVD diamond; in the cylindrical material, the center is CVD diamond, and a coil is rolled around the outer periphery of the CVD diamond, the coil has 2-5 layers in total, and each layer of the coil consists of 1-3 layers of copper foil and 1-3 layers of graphene.
[0008] The copper foil is a strip with a copper content of not less than 98wt.% and a thickness of 0.05~0.6mm.
[0009] Graphene is graphene film or graphene paper with a thickness of 2~300μm.
[0010] CVD diamond is a cylindrical single crystal or polycrystalline diamond with a diameter of 7~52mm and a thickness of 0.5~3mm.
[0011] The composition of each layer of coil is: 1-3 layers of graphene are stacked on each layer of copper foil; or 1-3 layers of graphene are stacked on every two layers of copper foil; or 1-3 layers of graphene are stacked on every three layers of copper foil.
[0012] A method for preparing the above copper-carbon-carbon thermal conductive material, the specific steps are as follows: 1) Stack the graphene and copper foil layer by layer and press them gently; 2) Trim the starting end of the roll into a bevel; 3) placing the outer cylindrical surface of the CVD diamond on the graphene surface, and gradually rolling up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing and sintering; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0013] The composition of each layer of coil is as follows: 1-3 layers of graphene are stacked on each layer of copper foil; or 1-3 layers of graphene are stacked on every two layers of copper foil; or 1-3 layers of graphene are stacked on every three layers of copper foil.
[0014] CVD diamond is in contact with graphene during rolling.
[0015] The graphene in direct contact with CVD diamond is 1-3 layers.
[0016] The sintering method is vacuum hot pressing, the temperature is 900~1100℃, and the pressure is 10~40MPa.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The high in-plane thermal conductivity of the graphene material of the present invention is achieved by rolling up the graphene material so that the heat conduction direction is changed from conduction between graphene surfaces to conduction within the surface, thereby greatly improving the thermal conductivity.
[0018] 2. The present invention improves the mechanical properties of the material by stacking and rolling the copper foil and graphene layer by layer, so that the material has good processability, so that it can be processed into the required size of the thermal conductive component after the material is prepared.
[0019] 3. The present invention sets an axis for the sheet material, which increases the rolling density of the center part while reducing the risk of sheet material breakage due to excessive force in the center, and also reduces the difficulty of rolling.
[0020] 4. Using CVD diamond as the axis can effectively improve the thermal conductivity of the center of the material. At the same time, by using CVD diamond in contact with graphene, the efficiency of heat dissipation from the center to the surrounding area is improved, effectively improving the uniformity of heat dissipation of the material.
[0021] 5. The product of the present invention can be rolled into the required size according to the actual required size, thus overcoming the problem that the single carbon-based thermal conductive material is often too small in size. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the copper foil and graphene stacked according to the present invention.
[0023] Figure 2 This is another schematic diagram of copper foil and graphene stacking.
[0024] Figure 3 This is a schematic diagram of copper foil and graphene after being rolled on the outer circle of CVD diamond.
[0025] Figure 4 yes Figure 3 Schematic diagram after grinding and cutting.
[0026] Figure 5 yes Figure 4 Schematic diagram after the copper frame is installed.
[0027] Among them: 1. copper foil, 2. graphene, 3. CVD diamond, 4. copper frame. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0030] like Figure 1 As shown, a copper-carbon-carbon thermal conductive material is characterized in that: the material is a cylindrical material formed by rolling copper foil 1 and graphene 2 along the outer circle of CVD diamond 3; in the cylindrical material, the center is CVD diamond 3, and a coil is rolled around the periphery of CVD diamond 3, and the coil is provided with 2-5 layers in total, and each layer of the coil is composed of 1-3 layers of copper foil 1 and 1-3 layers of graphene 2, that is: 1-3 layers of graphene 2 are arranged on every 1-3 layers of copper foil 1, and 1-3 layers of copper foil 1 are arranged above the graphene 2, and so on.
[0031] Furthermore, the copper foil 1 is a strip having a copper content of not less than 98 wt.% and a thickness of 0.05-0.6 mm.
[0032] Furthermore, the graphene 2 is a graphene film or graphene paper with a thickness of 2 to 300 μm.
[0033] Furthermore, the CVD diamond 3 is a cylindrical single crystal or polycrystalline diamond with a diameter of 7 to 52 mm and a thickness of 0.5 to 3 mm.
[0034] A method for preparing a copper-carbon-carbon thermal conductive material, wherein a copper foil 1 and a graphene 2 are stacked layer by layer, and then the stacked copper foil 1 and the graphene 2 are rolled around the outer circle of the CVD diamond 3 with a CVD diamond 3 as the axis. After rolling, the material is shaped by sintering, and then the material is machined into a desired size and a copper frame is covered on the side thereof. The specific steps are as follows: 1) Stack the graphene 2 and the copper foil 1 layer by layer and press them lightly; 2) Trim the starting end of the roll into a bevel; 3) placing the outer cylindrical surface of the CVD diamond 3 on the surface of the graphene 2, and gradually rolling up the stacked materials with the micro-axis of the CVD diamond 3; 4) Place the rolled material into a graphite mold for vacuum hot pressing and sintering; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame 4 is placed on its side to obtain a finished thermal conductive material.
[0035] Furthermore, the composition of each layer of the coil is: (1) 1 to 3 layers of graphene 2 are stacked on each layer of copper foil 1; or (2) 1 to 3 layers of graphene 2 are stacked on every two layers of copper foil 1; or (3) 1 to 3 layers of graphene 2 are stacked on every three layers of copper foil 1.
[0036] Furthermore, during rolling, the CVD diamond 3 is in contact with the graphene 2. More preferably, the graphene 2 directly in contact with the CVD diamond 3 is 1-3 layers.
[0037] Furthermore, the sintering method is a vacuum hot pressing method, the temperature is 900~1100℃, and the pressure is 10~40MPa.
[0038] Embodiment 1: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) stacking a layer of graphene 2 paper with a thickness of 100 μm and a layer of copper foil 1 with a thickness of 0.1 mm twice and lightly pressing them; 2) Trim the starting end of the roll into a bevel; 3) Place the outer cylindrical surface of a CVD single crystal diamond with a diameter of 15 mm and a thickness of 1.3 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond 3 micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 1000°C and a pressure of 30MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame 4 is placed on its side to obtain a finished thermal conductive material.
[0039] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: Embodiment 2: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) stacking two layers of graphene 2 films with a thickness of 50 μm and one layer of copper foil 1 with a thickness of 0.3 mm layer by layer and lightly pressing them; 2) Trim the starting end of the roll into a bevel; 3) Place the outer cylindrical surface of a CVD polycrystalline diamond with a diameter of 25 mm and a thickness of 1.5 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 1050°C and a pressure of 25MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0040] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: Embodiment 3: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) Stack a layer of 150 μm thick graphene 2 film paper and a layer of 0.2 mm thick copper foil twice and press them lightly; 2) Trim the starting end of the roll into a bevel; 3) Place the outer cylindrical surface of a CVD polycrystalline diamond with a diameter of 15 mm and a thickness of 1.5 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 990°C and a pressure of 30MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0041] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: Embodiment 4: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) Stack two layers of 100 μm thick graphene 2 film and one layer of 0.2 mm thick copper foil twice and press them lightly; 2) Trim the starting end of the roll into a bevel; 3) Place a CVD single diamond outer cylindrical surface with a diameter of 7 mm and a thickness of 0.5 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 900°C and a pressure of 20MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0042] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: Embodiment 5: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) Stack 3 layers of 5μm thick graphene 2 film paper and 1 layer of 0.1mm thick copper foil layer by layer and press them lightly; 2) Trim the starting end of the roll into a bevel; 3) Place the outer cylindrical surface of a CVD single crystal diamond with a diameter of 25 mm and a thickness of 2 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 950°C and a pressure of 30MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0043] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: Embodiment 6: The copper-carbon-carbon thermal conductive material of this embodiment is prepared by the following steps: 1) Stack three layers of 280 μm thick graphene 2 film paper and one layer of 0.6 mm thick copper foil four times and press them lightly; 2) Trim the starting end of the roll into a bevel; 3) Place the outer cylindrical surface of a CVD single crystal diamond with a diameter of 50 mm and a thickness of 3 mm on the surface of the graphene film paper, and gradually roll up the stacked materials with the CVD diamond micro-axis; 4) Place the rolled material into a graphite mold for vacuum hot pressing sintering at a temperature of 1000°C and a pressure of 30MPa; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame is placed on its side to obtain the finished thermal conductive material.
[0044] A batch of copper-carbon-carbon thermal conductive materials were prepared by this method, and 5 pieces were randomly selected for performance testing. The thermal conductivity of the thermal conductive materials was tested by a laser thermal conductivity meter. The thermal conductive materials were compared with the copper-diamond thermal conductive materials produced by the current traditional process under the same conditions. The comparison results are as follows: The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.
Claims
1. A copper-carbon-carbon thermal conductive material, characterized in that: The material is a cylindrical material formed by rolling copper foil (1) and graphene (2) along the outer circle of a CVD diamond (3); in the cylindrical material, the center is the CVD diamond (3), and a coil is rolled around the outer periphery of the CVD diamond (3), the coil has 2 to 5 layers in total, and each layer of the coil consists of 1 to 3 layers of copper foil (1) and 1 to 3 layers of graphene (2).
2. The copper-carbon-carbon thermal conductive material according to claim 1, characterized in that: The copper foil (1) is a strip material, has a copper content of not less than 98wt.%, and a thickness of 0.05-0.6mm.
3. The copper-carbon-carbon thermal conductive material according to claim 1, characterized in that: The graphene (2) is a graphene film or graphene paper with a thickness of 2 to 300 μm.
4. The copper-carbon-carbon thermal conductive material according to claim 1, characterized in that: The CVD diamond (3) is a cylindrical single crystal or polycrystalline diamond with a diameter of 7 to 52 mm and a thickness of 0.5 to 3 mm.
5. The copper-carbon-carbon thermal conductive material according to claim 1, characterized in that: Each layer of the coiled material is composed of: 1 to 3 layers of graphene (2) stacked on each layer of copper foil (1); or 1 to 3 layers of graphene (2) stacked on every two layers of copper foil (1); or 1 to 3 layers of graphene (2) stacked on every three layers of copper foil (1).
6. A method for preparing the copper-carbon-carbon thermal conductive material according to claims 1-5, characterized in that: The specific steps are as follows: 1) stacking the graphene (2) and the copper foil (1) layer by layer and lightly pressing them; 2) Trim the starting end of the roll into a bevel; 3) placing the outer cylindrical surface of the CVD diamond (3) on the surface of the graphene (2) and gradually rolling up the stacked materials with the micro-axis of the CVD diamond (3); 4) Place the rolled material into a graphite mold for vacuum hot pressing and sintering; 5) The sintered product is processed to the required size through cutting, grinding and other processes, and a copper frame (4) is placed on its side to obtain a finished thermal conductive material.
7. The method for preparing the copper-carbon-carbon thermal conductive material according to claim 6, characterized in that: Each layer of the coiled material is composed of: 1 to 3 layers of graphene (2) stacked on each layer of copper foil (1); or 1 to 3 layers of graphene (2) stacked on every two layers of copper foil (1); or 1 to 3 layers of graphene (2) stacked on every three layers of copper foil (1).
8. The method for preparing the copper-carbon-carbon thermal conductive material according to claim 6, characterized in that: During rolling, the CVD diamond (3) is in contact with the graphene (2).
9. The method for preparing the copper-carbon-carbon thermal conductive material according to claim 8, characterized in that: The graphene (2) in direct contact with the CVD diamond (3) is 1 to 3 layers.
10. The method for preparing the copper-carbon-carbon thermal conductive material according to claim 6, characterized in that: The sintering method is vacuum hot pressing, the temperature is 900~1100℃, and the pressure is 10~40MPa.
Citation Information
Patent Citations
Flake diamond-reinforced metal matrix composite and preparation method
CN105220049A
Spiral line reinforced metal matrix composite and manufacturing method thereof
CN105463346A
Preparation method for graphite and copper composite heat conduction material
CN107460483A
High-strength and high-conductivity copper-based composite material and preparation method thereof
CN111145960A
Two-dimensional carbon-metal configuration composite material and preparation method and application thereof
CN113355058A
